Developing Indonesian Digital-Skilled Teachers for Multicultural Education Into The Society 5.0 - Marjuni; Suyudi, Muhamad; Mahmudah, Ummi (Proceeding International Conference on Islam and Civilization (ICONIC), 2021)
This study identified the necessary competencies of digital and online teachers for face M.E. face Society 5.0. The data were analyzed using descriptive analysis of the M.E. that Indonesia aspires to, beginning with the history of global multicultural issues and the growth of multiculturalism in Indonesia. The study aims to explore specific fundamental issues, such as 1) How can education foster peaceful coexistence among Indonesia’s different ethnic groups? 2) What is the management strategy for establishing the legal framework governing M.E. implementation? 3). How can policymakers educate Indonesian teachers and school teachers to model critical intercultural education appropriate for their school environment? 4. How can a multicultural curricular system be used to integrate information, attitudes, and skills? 5) What will the future profile of digital teachers be in fighting for multiculturalism’s values? The research finds that 1). The Indonesian NES Law No. 20/2003 allows schools additional latitude and authority to promote intercultural education via religion and civic education. The government requires instructors to create unique and creative intercultural learning methodologies. Education can help ethnic groups cohabit peacefully in Indonesia. 2). There are still several obstacles, including the absence of explicit regulations governing how multiculturalism-based educational innovation has become its operational reference. 3). Training for leaders, educators, and teachers in need and held to the unit’s standards. The emphasis in global education is on treating others and the environment with dignity. A multicultural curriculum’s (M.C.) delivery is one of its seven pillars. Five curricular viewpoints show the ebb and flow of Indonesian educational developments. 4). To construct and mold M.C., citizenship and social responsibility must be intrinsic parts of the five primary curricular keys. To be democratic, one must engage in behaviors and attitudes that support that democratic process. The government and educational units need an effective assessment program to maintain accreditation as proof of academic units’ continual improvement. 5). A good teacher must be more than just a messenger of information. Technology will never take the place of mentoring, direction, and inspiration. Teachers are under increasing pressure to incorporate new technologies into their curricula. Becoming a tech-savvy educator requires the right tools and support from schools and governments.